Estrategia de enseñanza apoyada en tic para el desarrollo de habilidades metacognitivas en el área de la morfofisiología - Farías Ramos, Miguel Ángel (Universidad Antonio Nariño, 2023)
In the academic context it is usual to see students and teachers make use of the Internet in the teaching and learning processes; not only because of the ease of access to the network, but also because this access favors communication between people from different places when some of them cannot be present in person, not to mention the amount and diversity of information available, which increases exponentially more and more use. Some studies maintain that the student population prefers to search for information through the web to carry out their academic work, queries that can amount to 94% (Purcell, et al., 2012; Arango, Bringué, & Sádaba, 2010).